MENINGKATKAN KINERJA KARYAWAN MELALUI PERAN KEPEMIMPINAN, MOTIVASI DAN DISIPLIN KERJA - Indah Ayu Karlina; Rusnandari Retno Cahyani; Destina Paningrum (Universitas Sahid Surakarta, 2015)
Human resource represents the asset to an organization/company. Existence of Human Resource can't replaced by other resource. Efficacy of Human Resourcesupported by leadership role, motivation, work discipline and optimalization good performance.Research purpose is to knowing the influence of leadership role,motivation, and work discipline to employee performance Sahid University of Surakarta.